The Influence of Elementary School Students' Study Habits toward Motivation Achievement - Fitri Siti Sundari; Dadang Kurnia; Elly Sukmanasa; Lina Novita (Universitas Pendidikan Indonesia (UPI), 2020)
The purpose of this research is to determine the effect of learning habits on student achievement motivation. The research method is a causal approach implemented in V students in Cikaret 1 Elementary School, Bogor. Based on the calculation results of the regression equation analysis shows there is a positive influence between the two variables, this means that if the variable X rises if the variable Y rises. Based on the results of the Product Moment analysis showed a correlation coefficient of 0.77 and a coefficient of determination of 59% means that there is a very high correlation between study habits with student achievement motivation. If the study habits are high, the student achievement motivation will also be high and vice versa. The results of the analysis showed a positive relationship between learning habits variables and achievement motivation variables with the equation = 81.193 + 0.1174X, meaning that if learning habits experience an increase of one unit, then achievement motivation will increase by 0.1174. Furthermore, the correlation coefficient significance test obtained showed that tcount ttable with tcount = 11,797 while ttable 2,079. The conclusion of this study is that there is a positive and significant influence on elementary students' learning habits on achievement motivation. Furthermore, the coefficient of determination of 59% means that achievement motivation is influenced by study habits by 59%, while 41% of achievement motivation is influenced by other factors. meaning that if learning habits experience an increase of one unit, then achievement motivation will increase by 0.1174. Furthermore, the correlation coefficient significance test obtained showed that tcount ttable with tcount = 11,797 while ttable 2,079. The conclusion of this study is that there is a positive and significant influence on elementary students' learning habits on achievement motivation. Furthermore, the coefficient of determination of 59% means that achievement motivation is influenced by study habits by 59%, while 41% of achievement motivation is influenced by other factors. meaning that if learning habits experience an increase of one unit, then achievement motivation will increase by 0.1174. Furthermore, the correlation coefficient significance test obtained showed that tcount ttable with tcount = 11,797 while ttable 2,079. The conclusion of this study is that there is a positive and significant influence on elementary students' learning habits on achievement motivation. Furthermore, the coefficient of determination of 59% means that achievement motivation is influenced by study habits by 59%, while 41% of achievement motivation is influenced by other factors. The conclusion of this study is that there is a positive and significant influence on elementary students' learning habits on achievement motivation. Furthermore, the coefficient of determination of 59% means that achievement motivation is influenced by study habits by 59%, while 41% of achievement motivation is influenced by other factors. The conclusion of this study is that there is a positive and significant influence on elementary students' learning habits on achievement motivation. Furthermore, the coefficient of determination of 59% means that achievement motivation is influenced by study habits by 59%, while 41% of achievement motivation is influenced by other factors.